Financial Feasibility Analysis of an Autoclaved Aerated Concrete (AAC) Manufacturing Plant in East Kalimantan (Study Case of PT XYZ) - Paliling, Allensius; Soekarno, Subiakto (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study evaluates the financial feasibility of establishing an autoclaved aerated concrete (AAC) manufacturing plant in East Kalimantan, a region experiencing rapid construction growth driven by the development of Indonesia’s new capital city. The analysis is conducted using a discounted cash flow approach within a capital budgeting framework. The financial model incorporates detailed assumptions on capital expenditure, revenue projections, cost structure, and financing structure within a ten-year projection horizon. Key feasibility indicators include Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI), with the Weighted Average Cost of Capital (WACC) applied as the discount rate. The results indicate that the project is financially feasible, generating a positive NPV of IDR 104.738.902.831 and an IRR of 20.69%, exceeding the WACC of 10.07%, with a Payback Period of 5.3 years and a Profitability Index of 1,58. Overall, the findings suggest that the proposed AAC manufacturing plant is commercially viable, capable of supporting regional construction demand while significantly reducing cost dependency on inter-island AAC transportation from Java.